Performance evaluation of a prototype distributed NFS server - Avila, R. B.; Navaux, P. O. A.; Lombard, P.; Lebre, A.; Denneulin, Y. (Anais do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD); 2004: Anais do XVI Symposium on Computer Architecture and High Performance Computing, 2004)
A high-performance file system is normally a key point for large cluster installations, where hundreds or even thousands of nodes frequently need to manage large volumes of data. While most solutions usually make use of dedicated hardware and/or specific distribution and replication protocols, the NFSP (NFS Parallel) project aims at improving performance within a standard NFS client/server system. In this paper we investigate the possibilities of a replication model for the NFS server, which is based on Lasy Release Consistency (LRC). A prototype has been built upon the user-level NFSv2 server and a performance evaluation is carried out.